PERBANDINGAN ALAT BERMAIN MOTORIK KASAR DAN MEDIA MOTORIK HALUS TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA 5-6 TAHUN PAUD LABSCHOOL JEMBER - Wijaya Adi Putra (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2017)
In this study, researchers used a quantitative approach to design the type of comparative research, by comparing between two or more groups of a particular variable. The independent variables in this study is a tool to Play Motor Coarse and Fine Motor Media (X), while the dependent variable is the Cognitive Development (Y). In this study, respondents are children in group B second semester ECE Labschool Jember 2015/2016 school year. To determine the effect ofplaying comparisons of gross motor play and the media fine motor to the cognitive development of children in group B second semester ECE Labschool Jember  2015/2016 school year, the researchers used statistical methods of data analysis with Chi Kuadrat formula. Based on the results of research and discussion presented it can be concluded that the media fine motor further improve children'scognitive development compared with gross motor games. This is proved by the significant level of 5% value of Chi Kuadrat criticism is 3,841 less than the Chi Kuadrat empirical 18.17. Thus a significant means. So that the working hypothesis is accepted and the null hypothesis is rejected. So there is a comparison tool influence play gross motor and fine motor skills towards early childhood cognitivedevelopment and age group of 5-6 Year ECE Labschool Jember Semester Academic Year 2015/2016.